The seismic damage mechanism of Daliang tunnel by fault dislocation during the 2022 Menyuan Ms6.9 earthquake based on unidirectional velocity pulse input. (March 2023) - Chen, Pingliang; Geng, Ping; Chen, Junbo; Gu, Wenqi
Highlights: The displacement field of 2022 Menyuan earthquake was calculated and analyzed based on the finite fault model and Okada dislocation theory. The fault dislocation load was considered as a unidirectional harmonic velocity pulse. Seismic damage in tunnels across active faults has two modes of dislocation failure and impact failure. Abstract: Fault dislocation may cause severe damage to tunnel structures. A representative example is the severe damage of the Daliang Tunnel caused by the dislocation of the Lenglongling Fault in the 2022 Menyuan, Qinghai, China, Ms6.9 earthquake. The relative displacement on both sides of the fault during an earthquake is often assumed to be a quasi-static dislocation load, ignoring the dynamic effect. In this study, the dislocation load was considered as a unidirectional harmonic velocity pulse and the damage mechanism of the Daliang tunnel was studied. First, the background of this earthquake and the damage of Daliang tunnel is introduced. The characteristics of surface displacement in this earthquake are analyzed by finite fault model and Okada dislocation theory model, and the dislocation vector of Daliang tunnel is calculated. On this basis, a fault-tunnel FEM nonlinear dynamic model is established, in which unidirectional velocity pulse is used as input of dislocation displacement to consider the dynamic effect of fault dislocation. The study found that the Daliang tunnel was located in one of the regions with the largest dislocation displacement in this earthquake, and the tunnel structure was damaged as a result. The analysis of FEM model reveals that when a unidirectional velocity pulse is used as the load, the tunnel damage is consistent with reality, and the conventional method using the quasi-static dislocation as the load only reflects the dislocation effect of the fault displacement and ignores the impact effect. When the dislocation displacement is certain, the duration of the unidirectional velocity pulse is an important parameter; the shorter the duration, the greater the amplitude of unidirectional velocity pulse, resulting in more serious tunnel damage. The tunnel's failure mechanism near the fault can be divided into dislocation failure and impact failure. The dislocation failure is manifested by non-uniform dislocation displacement along the longitudinal direction of tunnel, which is mainly related to the amount of dislocation. The impact failure is manifested by crushing and invert uplift of the lining in cross-section, and it is related to the pulse duration.